PREDICTIVE VALUE OF UMBILICAL ARTERIAL BLOOD LACTATE IN NEONATES WITH MECONIUM-STAINED LIQUOR - FATIMA , K; ISHAQ , M; BIBI , M (Biological and Clinical Sciences Research Journal, 2023)
This research aims to determine the clinical and maternal variables contributing to increased lactate levels and determine the prognostic usefulness of umbilical cord blood lactate levels in neonates through meconium-stained liquor. The study was conducted between 01 June 2022 and 31 May 2023 at the Department of Neonatology, CMH Rawalpindi. This study included 100 newborns with meconium aspiration syndrome (MAS) in a thin cross-sectional design. Newborn babies received treatment at CMH Hospital throughout the approved period, and observations of umbilical cord blood have been obtained for lactate measurement and arterial blood gas analysis. Furthermore, information on post-delivery problems and neonatal features was retrieved using hospital records. The research included comprehensive statistical analyses, encompassing both Bivariate and multivariate evaluations, to pinpoint the variables linked to increased lactate levels and their potential predictive significance for unfavorable neonatal outcomes. This study included 720 unpaired samples of cord blood from the umbilical artery. The lactate result had an interquartile range of 4.0–6.2 mmol/L and a mean of 5.49 mmol/L (± SD 2.44 mmol/L). After birth, resuscitation was required for a considerably more significant number of neonates with increased lactate levels (25.1%) than for those who had lesser lactate levels (1.3%). At five minutes, Apgar scores of less than seven also showed a significant correlation between high lactate levels and a greater incidence of asphyxia (19.8%). Meconium-stained liquor (aOR=5.85), primigravidity (aOR=2.78), male sex (aOR=1.71), and oxytocic administration (OR=1.97) were factors linked to elevated lactate levels. The results highlight the prognostic significance of umbilical cord blood lactate levels in newborn outcomes, particularly while considering the necessity for resuscitation, asphyxia, and diagnosis such as hypoxic encephalopathy. Elevated lactate levels are more likely in cases where maternal and clinical variables are present, such as primigravidity and liquor stained with meconium. This study underscores the feasibility of including lactate measures from umbilical cord blood into standard evaluations of neonates, providing a valuable instrument for prompt identification and remediation. Prospective investigations and multi-center trials are necessary to confirm these results and investigate the long-term effects of increased lactate levels on newborn health.